The Analysis of the Impact of Energy and Environmental Policies of the European Union on the Economic Performance of Companies. Case Study in the Transport Sector - Monica Aureliana Petcu; Eduard Madalin Dinu; Irina Daniela Cismasu; Raluca Andreea Popescu-Predulescu (Amfiteatru Economic, 2023)
The macroeconomic reason and objectives, in a normative framework, reside to a large extent in the support, catalysis, and efficiency of activities at the microeconomic level, the gear through which they are built. Responsible behaviour at the macro and microeconomic level involves the dynamic revelation of dysfunctions and conflicts, generated within each sphere, in their relationship, as well as in the involved normative framework, in order to establish effective mechanisms for balance and development. The purpose of this approach is to analyse the micro-macroeconomic convergence from the perspective of the link between economic performance and energy consumption from the point of view of ensuring the necessary resources and the efficiency of their use, with impact on the environment. The study covers the transport sector at the level of the member countries of the European Union in the period 2011-2020, the collected data being processed with the regression method. The growth in energy efficiency and energy dependence are, against the background of the increase in the volume of activity, factors that lead to an increase in the gross operating rate. From the analysis, it emerges that the use of renewable energy to a greater extent, as a result of sustainable development, does not constitute a significant factor for improving the economic performance of companies in the transport sector. The contributions of the two-dimensional approach conducted consist of mediating the conflict between the objectives of economic profitability and the environmental constraints, targeting both the microeconomic level, through the analysis of the gross operating rate in correlation with energy consumption and CO2 emissions, as well as the macroeconomic level, constituting a benchmark in policies substantiation.
Keywords: E21; M21; O52; Q43; R49; 330; gross operating rate; energy efficiency; energy dependence; renewable energy; CO2 emissions.